A Study Of Work Ethic And Commitment Of Professional Teachers Advisor at SMA Negeri Kota Manado (2018) - Taher, Y (Universitas Negeri Manado, 2019)
The purpose of this research are: 1) to know work ethics counselor from the aspect of implementation of tasks SMA service in Manado City. 2) To know the effort / how to tutor students develop ethics and morals in SMA Negeri Manado. 3) To know professional commitment counselor in the running task in this school . 4) To determine the factors that inhibit a tutor increase work ethic and professional commitments. 5) To know the efforts have been made by a professionals tutor to overcome barriers to the implementation of the ministry in SMA Negeri of Manado City. This research uses qualitative approach. The sampling technique used is purposive sampling and snowball sampling. The main instrument in qualitative research is that the researchers themselves in the data collection are: 1). Observation 2). Interview, .3). Documentation. Data analysis technique used qualitative analytical technique. Teacher of professional counsellor to overcome barriers to the implementation of the ministry in SMA Negeri Manado?